PENYULUHAN KESEHATAN DALAM UPAYA MENCEGAH INFEKSI MENULAR SEKSUAL PADA REMAJA DI KECAMATAN SUKAWATI KABUPATEN GIANYAR - ida ayu, sri arjani; Mastra, I Nyoman (Poltekkes Kemenkes Denpasar, 2023)
Knowledge is the most important factor in shaping someone behavior or actions (over behavior). Behavior that is based on knowledge will usually be lasting, compared to behavior that is not based on knowledge. The purpose of this community-based service is to find out that a media booklet can increasing teenagers' knowledge in preventing STIs in Sukawati High School, Gianyar.There are 97 respondents who obtained this community-based service, the number of respondents aged 15 years as many as 6 people (6.19%), aged 16 years as many as 47 people (48.45%), aged 17 years as many as 39 people (40.21 %), aged 18 years as many as 5 people (5.15%). According to gender, there were 40 men (41.24%) and 57 women (58.76%). The results of counseling by filling out the questionnaire to determine the level of knowledge of respondents, before counseling by 37 people (38.14%) in the good category, 49 people (50.52%) in the sufficient category and 11 people (11.35%) in the less category. After counseling, all 97 respondents (100%) were in the good category.The conclusion from this community-based service is that the knowledge of High school in Sukawati Gianyar has increased after being provided with counseling in the form of media booklets. Suggestions are expected to teenagers’ in Sukawati Gianyar to increase knowledge by reading more and looking for information about sexually transmitted infections.Keywords : Media booklet, Knowledge,STIs